STUDY OF CONDENSING ECONOMIZERS IN INDUSTRIAL APPLICATIONS (International Journal of Engineering Sciences & Management Research, 2017)
Condensing economizers increase the thermal efficiency of boilers by recovering sensible and latent heat from exhaust gas. A considerable amount of waste heat in boiler flue gases is in the form of latent heat of water vapor. This energy cannot be recovered until the flue gases are cooled to a temperature below the dew point. These economizers are currently being used commercially for this purpose in a wide range of applications. Performance is dependent upon application-specific factors affecting the utility of recovered heat. Condensing economizers can also capture flue gas particulates. In this paper, the primary focus is on introduction of condensing economizer’s for efficiency improvement of natural gas fired boiler. The secondary focus of this paper is to reduce or to control the particulate emission from natural gas fired boiler.